Résolution de petits systèmes algébriques par la MAN sous Matlab - Cochelin, Bruno; Pérignon, Franck (European Journal of Computational Mechanics, 2004)
This paper presents a Matlab software for the continuation of solutions of algebraic systems with parameters. We recall the principle of continuation with the MAN with an example, and we progressively introduce all the routines of the program. Next, we discuss the problem of finding a first solution point on the branch, and the problem of jumping onto another branch. A few additional examples are given to insist on a crucial point : writing the equation in a quadratic framework.